2017
DOI: 10.1161/strokeaha.116.016183
|View full text |Cite
|
Sign up to set email alerts
|

Disparities and Trends in Door-to-Needle Time

Abstract: Background and Purpose In the US, about half of acute ischemic stroke patients treated with tissue plasminogen activator (tPA) receive treatment within 60 minutes of hospital arrival. We aimed to determine the proportion of patients receiving tPA within 60 minutes (DTNT≤60) and 45 minutes (DTNT≤45) of hospital arrival by race/ethnicity and sex and to identify temporal trends in DTNT≤60 and DTNT≤45. Methods Among 65,654 AIS admissions in the NINDS-funded FL-PR Collaboration to Reduce Stroke Disparities (CReSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…13 Furthermore, the FSR identified that women and non-Hispanic Black individuals were more likely to receive delayed acute stroke care including longer door-to-needle and door-to-CT times. 20,21 Our findings add to the aforementioned data showing that women and minority groups tend to receive suboptimal stroke care, and suggest that antiplatelet therapy selection in the acute phase may contribute further to the higher readmission and mortality rates reported in these populations. 22,23 Quality improvement interventions have shown to be effective improving adherence to stroke care performance metrics and to reduce disparities.…”
Section: Discussionsupporting
confidence: 68%
“…13 Furthermore, the FSR identified that women and non-Hispanic Black individuals were more likely to receive delayed acute stroke care including longer door-to-needle and door-to-CT times. 20,21 Our findings add to the aforementioned data showing that women and minority groups tend to receive suboptimal stroke care, and suggest that antiplatelet therapy selection in the acute phase may contribute further to the higher readmission and mortality rates reported in these populations. 22,23 Quality improvement interventions have shown to be effective improving adherence to stroke care performance metrics and to reduce disparities.…”
Section: Discussionsupporting
confidence: 68%
“…Acute care metrics including door to needle time have been shown to differ according to race, with many studies showing longer door to needle time in Black compared with White patients. 29,30 Other studies have shown delayed wait times after hospital arrival for Black and Hispanic patients compared with White patients. 31,32 Further study of the role of structural racism and implicit bias on under-utilization of EVT for ischemic stroke patients is needed.…”
Section: Discussionmentioning
confidence: 99%
“… 13 The PHANTOM study in Berlin demonstrated that the use of an ambulance‐based CT scanner followed by thrombolysis was safe and significantly increased the thrombolysis rate (32.6% vs 21% for standard care) and reduced the alarm‐to‐treatment time by a mean of 25 minutes. 14 The second solution could be to reduce the DTN time via a further decrease in the DIT, which was still longer than 25 minutes for more than half of the patients. Our results contrasted with those of interventional and observational studies, which reported a consistent decrease in the DIT.…”
Section: Discussionmentioning
confidence: 99%